Stress, Satisfaction and Militancy Among Canadian Physicians - Burke, Ronald J. (Relations industrielles / Industrial Relations, 1995)
A recent study utilized a stressor-strain framework to understand physician militancy in Canada. Data were collected from 2,584 physicians in 1986 using questionnaires. Four militant attitudes or activities were considered: 1. approval of binding arbitration in the event of deadlocks in fee negotiations with governments, 2. approval of withdrawal of services in the event of inadequate income settlements, 3. approval of the reconstitution of medical associations as labor unions, and 4. whether they had participated in an organized job action involving withdrawal of services.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Demographics; Job satisfaction; Labor Unions; Physicians; Psychology; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Stress; Studies